Development of small molecule probe for screening of bacterial resistant enzyme and their biomedical applications - Chan, Hui Ling (2018)
The work in this thesis has been aimed towards development of a small molecular probe for the screening of bacterial resistant enzymes. This thesis is divided into three main parts. Part I incorporates an introduction to gram positive and negative bacteria and its cell structure, β-lactam antibiotics with a brief insight into various core structure that drugs commonly consist of, β-lactamase enzyme mechanisms and the classifications, recent development in the use of small molecular probe for β-lactamase activities monitoring and imaging, as well as the current gaps and proposed work. Part II disclosed on a covalent labelling approach towards imaging AmpC β-lactamase activity on bacteria cell wall. Part III encloses the experimental data and references (Chapter III).